Propuesta De Comercio Electrònico Para La Empresa Comercializadora De Productos Y Servicios Para Mascotas, PETCOL (2021)
This research aims to propose a change in the business model of the marketing of pet products taking as a starting point the company Petcol that has been in the market for 20 years, being a leader in the industry and providing experiences, products and quality services. For the job you will gather information and background of previous studies related to e-commerce, through to the design of the canvas from its concept and utility explained in the theoretical framework, will provide the necessary information on the applicability of e-commerce, to this company